Pemantauan Lapangan Sistem Penerangan Tenaga Surya 6 x 50 Wp di Sleman - Nadjib, Muhammad (Jurnal Semesta Teknika, 2011)
Solar module and battery are important components in photovoltaic systems. These components have higher investment cost compared to controller device, lamp, cable, and the frame. Currently, there are six of 50 Wp of solar lighting systems (SLS) installed for cowshed lighting purpose in Sleman. The aim of this research is to investigate the pattern of electricity usage in SLS and to assess its performance, especially in the solar modules and their batteries after two months period of operation. The output voltage and current of solar module, the voltage of charging battery, the load consumption time, and the battery voltage at the end of charging and discharging were measured. The data were analyzed to determine the output power of solar module, average daily load, system performance ratio, and battery performance. It was revealed that the average daily load and performance ratio are 7.26 Ah/day and 49% respectively. Whilst at the end of charging of the battery is 100%, the maximum depth of discharge is 18.03% and its average efficiency is 59.85%. Overall, the SLSs have been well-operated; the solar module has produced electricity and all of the batteries were fully charged from the daily sunlight. However, it appears that the level of electric energy usage is still low. To increase the SLSâs efficiency it is recommended to optimize the usage of the produced electricity by intensifying livestock handling during night time. This solution also needs periodical monitoring of the SLSs which in turn will increase their lifetime.